Bank Competition, Financial Dependence, and Economic Growth in the Gulf Cooperation Council - Caggiano, Giovanni; Calice, Pietro (World Bank, Washington, DC, 2016)
The relationship between bank competition, firm access to finance, and economic growth is a much debated topic in the economic literature and in policy circles. This paper uses a panel of 23 manufacturing sectors over 2002-10 to investigate the impact of bank competition on industry growth in the Gulf Cooperation Council economies. The results show that greater competition allows financially dependent firms to grow faster. In addition, the results show that lower restrictions on banks’ permissible activities, better credit information, and greater institutional effectiveness mitigate the damaging impact of low competition. These results are robust to a variety of checks. The findings suggest that improving bank competition should be an important aspect of the financial sector development agenda in the Gulf Cooperation Council.